Ethiopia strategy support program (ESSP) 2013 - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
The Ethiopia Strategy Support Program (ESSP) is a collaborative program undertaken by the International Food Policy Research Institute (IFPRI) and the Ethiopian Development Research Institute (EDRI).